Audiological Findings of Speech Perception in Noise Test and Speech, Spatial, and Qualities of Hearing Scale Questionnaire in Patients with Chronic Kidney Disease - Ahmad Reza _Zamani; Sima Tajik; Somayeh Falahzadeh; Mina Bandad; Seyyed Mohammad Reza Taghavi; Farshid Oliaei (Shiraz University of Medical Sciences, 2023)
Background: The study aims to investigate the impact of chronic kidney diseases (CKD) on the auditory processing abilities of patients, including uremic neuropathy. The impairment of auditory processing may result in communication, social, and emotional problems in their lives. Accordingly, this study analyzes the communication abilities and speech perception of noise in CKD patients to identify potential auditory disorders rapidly.Methods: In this cross-sectional-comparative study, the authors randomly selected 30 CKD patients and 29 normal adults aged 20-55, all of whom had normal peripheral hearing. The participants underwent the consonant-vowel (CV) test with five signal-to-noise ratios (SNR) and silence. Additionally, the participants completed the speech, spatial, and qualities of hearing scale questionnaire (SSQ), which consisted of three subscales. The scores of the two groups were compared using the Mann-Whitney U test.Results: In both groups, the recognition scores for consonant-vowel decreased as the noise level increased. However, the normal group consistently outperformed the CKD patients at all noise levels. Regarding the three subscales of the SSQ, the patients obtained lower scores than the normal group, but this difference was not statistically significant.Conclusions: Chronic renal failure appears to have a negative impact on speech perception abilities in noise, suggesting auditory neurological involvement in CKD. Although patient self-assessment did not indicate any speech processing disability, conducting regular and periodic assessments of central hearing in CKD patients is still advisable. Early diagnosis of hearing disability can help mitigate its consequences, and appropriate rehabilitation measures should be taken if a disability is detected.